APLIKASI TRYOUT UJIAN NASIONAL SEKOLAH MENENGAH PERTAMA BERBASIS WEB - Uro Abdulrohim; Bayu Rohmat Desplantika Sukmana (JURTIK:Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2020)
The national examination tryout in 2018 requires a technical change, considering that the current national exam is computer-based, it is necessary to make an application for the national examination tryout which is a test balancer that will be conducted by students. The application of the national examination tryout is a technical description of examination using a computer. This national examination tryout application needs to be in every education agency, as well as in SMP Yadika Cicalengka. This is all because in addition to require material training, students also need technical training. Given the computer-based national examination technical training from Dinas Pendidikan is very lack. So this application can help students in carrying out technical training exams using computer. This application was formed using php program language with a framework from codeigniter, css and bootstrap. The database used is mysql, the questions entered are questions originating from ninth grade student at SMP Yadika Cicalengka. With the application of this National Examination tryout, students will more oftem conduct technical training on exams using computer. Especially in term of examinations. With the frequent use of this application will help students to increase self-confidence when doing on the tryout and real national exams. Keywords : Tryout, PHP, Framework, Codeigniter, CSS, Bootstrap, MySql